Developing Junior High School Students’ Competencies through ICT-Based Learning Strategies - Sugih Nurezki; R. Supyan Sauri (At Turots: Jurnal Pendidikan Islam, 2026)
This research aims to deeply understand the implementation of ICT-based learning model strategies in developing student competencies at SMPN 2 Pacet, Bandung Regency. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, direct observations, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that comprehensive needs identification including hardware infrastructure, computer laboratories, digital teaching materials, teacher human resource development, continuous training, technical support, and student readiness serves as the foundation for designing the learning model. The designed model integrates Project-Based Learning, Flipped Classroom, and Blended Learning, emphasizing local context and student needs. Its implementation transforms teachers' roles into facilitators and mentors, fosters an active and collaborative learning environment, and significantly enhances students' competencies in critical thinking, collaboration, and digital literacy. Evaluation reveals improvements in academic performance and intrinsic motivation among students, aligning with Generation Z's learning characteristics. The study concludes that a comprehensive, context-sensitive, and pedagogical approach to ICT-based learning implementation, supported by sustainable infrastructure and teacher development, can substantially boost student competencies and engagement.